Ensuring a healthy approach to long‐term weight management: Review of the Slimming World programme. Issue 3 (22nd August 2019) - Coe, S.; Spiro, A.; Lockyer, S.; Stanner, S.
Abstract: Weight management programmes have been shown to be effective interventions that encourage clinically relevant weight loss. The aim of a weight management programme is not only to achieve weight loss, but also to support long‐term weight maintenance and for that reason their suitability in helping people to meet the key dietary recommendations for health must be considered. The British Nutrition Foundation was asked to investigate whether the Slimming World weight management programme is consistent with current nutrient and food‐based recommendations, and whether Slimming World members following the programme are typically eating diets meeting these recommendations in the 'real world'. This was to help inform any potential refinements to their dietary approach. A three‐stage approach included a review of Slimming World's dietary approach resources, nutritional analysis of Slimming World's example menu plans and dietary analysis of 40 7‐day weighed food diaries completed by adult female Slimming World members. The Slimming World dietary approach reflects many of the main messages in the UK's Eatwell Guide and generally accepted healthy eating advice. Several observations were made with indications for potential changes in relation to key food groups. Nutritional analysis of the 7‐day menu plans suggests that a Slimming World member following a provided example menu plan could meet many of the UK dietary recommendations that were analysed in this review. Food diary analysis suggests the Slimming World study sample on average met dietary recommendations for total fat, saturated fat, calcium, salt and 5 A DAY. In comparison, national dietary surveys report that the average UK adult female population meets the total fat and calcium recommendations, but is not meeting the recommendations for saturated fat, salt and 5 A DAY. The study sample did not meet the recommendations for intakes of fibre and free sugars and oil‐rich fish, but these were still closer to recommendations than the average UK adult female population. High intakes of red and processed meat and alcohol were observed amongst some of the study sample. Overall, the findings suggest that despite a reduction in energy intake, adult females following this weight management programme may be consuming a diet that more closely meets UK dietary guidelines when compared with the average UK adult female population.